Possession Zone as a Performance Indicator in Football. The Game of the Best Teams - Casal, Claudio A.; Maneiro, Rubén; Ardá, Toni; Marí, Francisco J.; Losada, José L. (Frontiers in Psychology, 2017)
Possession time in football has been widely discussed in research but few studies have analyzed the importance of the field area in which possession occurs. The objective of this study was to identify the existence of significant differences in the field zone of ball possession between successful and unsuccessful teams and to acknowledge if the match status modulates the possession model. To this end, 2,284 attacks were analyzed corresponding to the matches in the final phase of the UEFA Euro 2016 France, recording possession time and field zone in which possession occurred. Video recordings of matches were analyzed and coded post-event using notational analysis. We have found that successful offensive game patterns are different from unsuccessful ones. Specifically, field zone in which major possession occurs changes significantly between successful and unsuccessful teams (x 2 = 15.72, p < 0.05) and through Welch's T significant differences were detected in possession time between successful and unsuccessful teams (H = 24.289, p < 0.001). The former are caracterized by longer possession times, preferably in the middle offensive zone, on the other hand, unsuccessful teams have shorter possession times and preferably on the middle defensive zone. Logistic regression also allowed us to identify that greater possession in the middle offensive zone is a good indicator of success in the offensive game, allowing us to predict a greater chance of victory in the match. Specifically, every time the teams achieve possession in the middle offensive zone, the chance of winning the match will increase 1.72 times and, the probability of winning the match making longer possessions in the middle offensive zone is 44.25%. Applying the Kruskal-Wallis test we have also been able to verify how match status modulates the teams possession time, specifically, when teams are winning they have longer possessions x 2 = 92.628, p = 0.011. Results obtained are expected to help gain more knowledge about successful offensive game models, as well as performance factors of the offensive phase, which will allow teams to optimize their training process and performance during the match.